Coronary vasospasm complicating atrial fibrillation ablation: a case report and review of the literature. Issue 4 (3rd July 2020) - Guragai, Nirmal; Rampal, Upamanyu; Vasudev, Rahul; Bhandari, Pragya; Prakash, Atul; Virk, Hartaj; Bikkina, Mahesh; Fayez, Shamoon
ABSTRACT: Radiofrequency ablation is one of the alternative treatment strategies in patients with atrial fibrillation. With the increasing number of such ablation procedures being performed it is important for the physicians to be aware of the associated complications. We present a very rare case of severe triple coronary vessel spasm during radiofrequency catheter ablation. The procedure was complicated by cardiac arrest secondary to ventricular fibrillation and cardiogenic shock requiring subsequent management with a temporary mechanical circulatory support device. Multi-vessel spasm is a rare and life-threatening complication leading to ventricular fibrillation and cardiac arrest. One should be extra vigilant in monitoring patients during extensive ablations and the procedure should be terminated at the earliest signs of ischemia in order to prevent this rare but fatal complication.